2010
DOI: 10.1007/978-1-60761-789-1_29
|View full text |Cite
|
Sign up to set email alerts
|

FISH on Chromosomes Derived from the Snail Model Organism Biomphalaria glabrata

Abstract: The application of fluorescence in situ hybridization (FISH) for the mapping of single copy genes onto homologous chromosome has been integral to vast number genome sequencing projects, such as that of mouse and human. The chromosomes of these organisms are well-studied and are the staple resource of most of the early studies conducted in cytogenetics. However, there are now protocols for analyzing FISH probes in a number of different organisms on both metaphase and interphase chromosomes.Here, we describe the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…FISH was performed as previously described with BAC DNA being labelled with biotin using nick translation and visualised via streptavidin conjugated to cyanine 3. After denaturation of the sample and probe, slides were placed at 37°C overnight to facilitate hybridisation [15], [48].…”
Section: Methodsmentioning
confidence: 99%
“…FISH was performed as previously described with BAC DNA being labelled with biotin using nick translation and visualised via streptavidin conjugated to cyanine 3. After denaturation of the sample and probe, slides were placed at 37°C overnight to facilitate hybridisation [15], [48].…”
Section: Methodsmentioning
confidence: 99%
“…Fluorescence in situ hybridisation (FISH) was performed using a probe derived from B. glabrata Bacterial Artificial Chromosome (BAC) libraries for the PIWI locus. The DNA probe was labelled by nick translation (BioNick Invitrogen, UK) as described [36,37] and incubating for 45-50 mins. The probe was precipitated with 1μg of labelled BAC DNA) [36], 80 μg of B. glabrata genomic DNA and 9 μg of herring sperm DNA.…”
Section: Examining Genome Organization Relocation Of the Piwi Locus In Susceptible And Resistant Snails Following Exposure To S Mansoni Mmentioning
confidence: 99%
“…This result is not entirely surprising since previous studies point to the plasticity of the B. glabrata genome as in other molluscs that showed difficulties in microsatellite marker development (McInerney et al, 2010). In addition, we have shown previously in B. glabrata embryonic cell lines (isolates 1 and 2) that this snail can display extensive aneuploidy, extending the normal diploid number of 36 chromosomes ( n = 18) (Odoemelam et al, 2010). Moreover, the basic chromosome number of planorbidae snails, including B. glabrata , can exhibit diploid, tetraploid, hexaploid and even octoploid levels of polyploidy (Patterson and Burch, 1978; Goldman et al, 1984; Odoemelam et al, 2009).…”
Section: Resultsmentioning
confidence: 67%
“…Furthermore, because these markers were developed based on expressed sequences, we hope a novel gene silencing RNA interference (RNAi) soaking method that we have recently developed (Knight et al, 2011b) will help to reveal the function of these identified genes as linked to B. glabrata susceptibility and resistance to S. mansoni infection. In addition, using the cloned markers as probes, corresponding bacterial artificial chromosomes (BACs) have now been identified and are currently being utilised (Adema et al, 2006) for the physical mapping of ex vivo B. glabrata chromosomes (Odoemelam et al, 2009, 2010). …”
Section: Resultsmentioning
confidence: 99%